2012
DOI: 10.1093/molbev/mss236
|View full text |Cite
|
Sign up to set email alerts
|

The Rhizome of the Multidrug-Resistant Enterobacter aerogenes Genome Reveals How New “Killer Bugs” Are Created because of a Sympatric Lifestyle

Abstract: Here, we sequenced the 5,419,609 bp circular genome of an Enterobacter aerogenes clinical isolate that killed a patient and was resistant to almost all current antibiotics (except gentamicin) commonly used to treat Enterobacterial infections, including colistin. Genomic and phylogenetic analyses explain the discrepancies of this bacterium and show that its core genome originates from another genus, Klebsiella. Atypical characteristics of this bacterium (i.e., motility, presence of ornithine decarboxylase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 76 publications
2
99
0
1
Order By: Relevance
“…In K. pneumoniae, the resistance to polymyxin is due to increased production of capsular polysaccharides (61). Recently, it has been demonstrated that in Acinetobacter baumannii or in Enterobacter aerogenes, acquired resistance to colistin may also be due to mutations in the pmrA-pmrB two-component systems (62,63). Finally loss of LPS production by mutations in the three genes lpxA, lpxC, and lpxD has been associated with the resistance to Acinetobacter baumannii (64).…”
Section: Discussionmentioning
confidence: 99%
“…In K. pneumoniae, the resistance to polymyxin is due to increased production of capsular polysaccharides (61). Recently, it has been demonstrated that in Acinetobacter baumannii or in Enterobacter aerogenes, acquired resistance to colistin may also be due to mutations in the pmrA-pmrB two-component systems (62,63). Finally loss of LPS production by mutations in the three genes lpxA, lpxC, and lpxD has been associated with the resistance to Acinetobacter baumannii (64).…”
Section: Discussionmentioning
confidence: 99%
“…Polymyxin Activity, Susceptibility, and Resistance Clinical Microbiology Reviews ter aerogenes (121), and Salmonella enterica (122,123) (Table 3). These mutations are responsible for constitutive activation of the PmrAB two-component system, leading to upregulation of the pmrCAB operon, the pmrHFIJKLM operon, and the pmrE gene, and thus to the synthesis of pEtN and L-Ara4N and their transfer to lipid A (Fig.…”
Section: Fig 3 Regulation Pathways Of Lps Modifications In Klebsiellamentioning
confidence: 99%
“…We speculate that the intercommunity CU bias we observe may be a consequence of an extensive exchange of genetic information in an environment, up to and including the level that is the strongest selection force for CU optimization-the shared tRNA pool (57,58). This in turn can be considered beneficial in particular for lifestyle-specific genes.…”
Section: Possible Mechanisms For the Cause Of Cu Bias In Metagenomesmentioning
confidence: 88%